History Teachers' Social Construction of History Learning in the 2013 Curriculum in High Schools in Semarang Regency - Fakhmi, Shinta; Atmaja, Hamdan Tri (Indonesian Journal of History Education, 2022)
The purpose of this study is to describe the social construction of the history teacher of the 2013 curriculum, the implementation of the 2013 curriculum, and the constraints on implementing the 2013 curriculum in history learning at high schools in Semarang Regency. This research includes qualitative data collection techniques through in-depth interviews, documents, and observations. This study's analysis technique uses data collection, reduction, presentation, and conclusion. This study found that in applying the 2013 curriculum in learning history, the social construction of the history teacher 2013 curriculum in high schools in the Semarang district varied due to the dialectical process teachers experienced through different experiences and influenced by several factors. In implementing the 2013 curriculum on learning, the teacher is adjusted to the characteristics of the school, school facilities, and infrastructure, and the characteristics of students applying the 2013 curriculum present various obstacles. Constraints faced by teachers include student activeness, lack of literacy, use of learning models and methods, and lack of training for teachers to help teachers understand the application of the 2013 curriculum in learning.